Collodion newborn with dehydration fever: A rare case report (Indian Journal of Case Reports, 2020)
Ichthyosis is a rare congenital disorder of the skin characterized by the presence of extra covering of tough film-like membrane over the skin leading to fissure formation on stretching. Clinically, newborns present with a membrane with fissures, ectropion, eclabium, and hypoplastic digits. Breakdown of the membrane makes newborns more prone to fluid loss, dehydration, electrolyte imbalance, body temperature instability, and infections leading to high mortality. Here, we report the case of a newborn with this condition presenting with fever, dyselectrolytemia, and dehydration after 48 h of birth managed as dehydration fever after excluding sepsis.